Supplementation of fetal bovine serum increased the quality of in vitro fertilized porcine embryo - Biswas, Dibyendu; Hyun, Sang Hwan (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: The present study aimed to explain the effect of fetal bovine serum (FBS) on the in vitro production of porcine embryos and the molecular effects of FBS on the growing of porcine embryos. Materials and Methods: Immature porcine oocytes were matured and fertilized in vitro. The resulting zygotes were cultured in porcine zygotic medium-3- until day 7 and FBS was added on day 4. Without FBS, it was treated as a control group. Quantitative real-time PCR and 2′,7′-dichloro-dihydro-fluorescein diacetate (H2DCFDA) molecular staining techniques were used to detect the expression patterns of apoptosis-associated genes and the accumulation of reactive oxygen species (ROS), respectively. Paired student’s t-test was used by GraphPad Prism statistical software. Results: FBS supplementation boosted blastocyst (BL) development and total cell count per BL substantially (p < 0.05). However, hatching and hatched BLs also increased in the FBS-treated group compared to the control. We also found that ROS accumulation in FBS-treated embryos was significantly reduced (p < 0.05) compared to the control group. The expression of the anti-apoptotic gene BCL-2 was significantly increased in FBS-treated BLs, but the pro-apoptotic gene, caspase-3 expression, was significantly reduced in FBS-treated BLs. Conclusion: Our results suggest that FBS supplementation in porcine culture media could increase porcine embryo production by decreasing ROS accumulation and increasing the anti-apoptotic gene expression in developing BLs. J. Adv. Vet. Anim. Res., 8(4): 589-596, December 2021 http://doi.org/10.5455/javar.2021.h549